Assessment of Maternal and Child Health Outcomes and Associated Risk Factors in Pakistan - Maheshwari, Jai Dev; Khan, Sayed; Munawar, Ammar; Zarak Khan, Muhammad; Khan, Abbas; Afzal, Bilal (Journal of Neonatal Surgery, 2025)
Introduction: Maternal and child health is one of the biggest public health issues in Pakistan where vulnerable groups are still exposed to preventable morbidity and mortality. Socioeconomic inequalities, poor healthcare access, and ineffective antenatal care are also some of the factors that help increase adverse outcomes. The purpose of the given study was to measure maternal and child health outcomes and determine the risk factors related to these outcomes in Pakistan. Methodology: The study was a community-based cross-sectional analytical research done between January and June 2025 in a group of 650 women aged 15-49 years who had given birth in the last five years. Multistage stratified sampling method was applied. Structured interviews were used to collect data. The sample size was computed on the basis of one population proportion formula with 95 percent confidence level and 5 percent margin of error. The descriptive statistics were calculated and Chi-square test, independent t -test, and ANOVA were used to evaluate the associations. When studying independent predictors, a multivariable logistic regression was conducted where p 0.05 was taken as statistically significant. Results: Pregnancy-related complications were reported in 27.4% of women. Low birth weight (19.5%), incomplete immunization (23.8%), and stunting (31.7%) were common child health outcomes. Inadequate antenatal care, rural residence, low maternal education, high parity, and low household income were significantly associated with adverse maternal and child outcomes in multivariable analysis. The incidence of pregnancy-related complications was 27.4 percent among women. The common child health outcomes were low birth weight (19.5%), incomplete immunization (23.8%), and stunting (31.7%). Poor maternal and child outcomes were closely linked with poor maternal and child health in multivariate analysis to poor antenatal care, rural dwellers, maternal low level of education, high parity, and poor household income. Conclusion: Mother and child mortality rates and morbidity are also poor, especially in the socioeconomically disadvantaged and rural groups. It is important to enhance antenatal care coverage and deal with social determinants in order to enhance health outcomes.